Genetics and Epigenetics in Complex Diseases (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Many of the most common diseases are influenced by a combination of multiple factors, which include environmental effectors as well as genetic and epigenetic variations. Therefore, these diseases are grouped under the term “complex” diseases because, from the point of view of genetics, they cannot be explained by simple Mendelian inheritance. The aim of this special issue was to identify genetic and epigenetic factors involved in such diseases in order to improve not only the knowledge of risk factors for those diseases, which could be of help for prevention, but also the understanding and characterization of each disease and to optimize and personalize the treatment.